The demand for news: Accuracy concerns versus belief confirmation motives - Felix Anand Chopra; Ingar Haaland; Christopher Roth (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We examine the relative importance of accuracy concerns and belief confirmation motives in driving the demand for news. In experiments with US respondents, we first vary beliefs about whether an outlet reports the news in a right-wing biased, left-wing biased, or unbiased way. We then measure demand for a newsletter covering articles from this outlet. Respondents only reduce their demand for biased news if the bias is inconsistent with their own political beliefs, suggesting a trade-off between accuracy concerns and belief confirmation motives. We quantify this trade-off using a structural model and find a similar quantitative importance of both motives.
Keywords: D83; D91; L82; 330; News Demand; Media Bias; Accuracy Concerns; Belief Confirmation